Socio-Ecological Justice in Waste Governance: Community Resilience in Peri-Urban Piyungan, Yogyakarta - febrian, Silvia (Journal of Society Bridge, 2025)
This study explores the socio-ecological injustices embedded in urban waste governance, focusing on the overburdened Piyungan Final Disposal Site (TPA) in Yogyakarta, Indonesia. Despite the official declaration of the facility's overcapacity in 2024, it persists in operating under emergency conditions in 2025, exerting a disproportionate impact on nearby peri-urban communities. The present study employs a socio-ecological justice theoretical framework that emphasizes distributive, procedural, and recognitional dimensions to explore the exacerbation of spatial inequalities by policy failures, governance dissonance, and lack of public participation. The study utilizes qualitative methodologies, encompassing document analysis, media reports, and secondary interviews, to elucidate systemic exclusion of affected residents from decision-making processes and the absence of sustained compensatory mechanisms. Concurrently, the research identifies bottom-up resilience strategies, including citizen-formed waste cooperatives and media-based advocacy. The findings indicate that sustainable urban development in the Global South cannot rely solely on technocratic or green branding initiatives. Rather, it must address more profound political and ethical questions concerning environmental justice, recognition, and community agency. This paper calls for a paradigm shift toward inclusive governance that repositions peri-urban citizens as co-architects of equitable waste management.